The impact of development and malaria control activities on its vectors in the Kinabatangan area of Sabah, East Malaysia - Vythilingam, Indra; Chan, Seng Thim; Shanmugratnam, C.; Tanrang, H.; Chooi, K.H. (Elsevier, 2005)
A study was carried out from July 2001 until January 2003 in the Kinabatangan area of Sabah, part of Borneo island, where malaria used to be mesoendemic. Vector surveys determined that Plasmodium falciparum was the predominant species and Anopheles balabacensis the primary vector. Malaria cases have dropped drastically over the years but P. falciparum is still predominant. In the present study, Anopheles donaldi was the predominant species and was positive for sporozoites. Although An. balabacensis was present, none were infective. An. donaldi bite more outdoors than indoors and have a peak biting time from 18:00 to 19:00 h when most people are still out of their homes. An integrated malaria control programme along with area development has helped in the control of malaria and its vector.